The doctrine of the independence of the judiciary / Mohd Roslan Mahayudin - Mahayudin, Mohd Roslan (Faculty of Law, 1982)
The Federal Constitution which as the Malayan Constitution came into force twenty five years ago, has proved to be a strong foundation on which to base a system of government capable of securing an efficient executive sensitive to the need for political stability without which there can be no economic stability and no prosperity for the newly independent nation. There is no doubt that since 31st. August 1957, where Malaysia achieved its independence the country has gone from strength to strength, as can be seen especially in the economic Field, also social and politic. The most dramatic ecidence is the value of Malaysian dollar which is today worth in terms of sterling double what it was at Independence. Many factors have been responsible for the steady progress made by the country in so many areas! Not least in the contribution made by the judiciary that has quietly maintained the supremacy of the Constitution and the rule of law, and determined the matters that come up before it fairly and impartially without fear or favour. The reputation that it enjoys of being able to decide without interference from the executive or the legislature, or indeed from anybody, contributes to confidence on the part of the members of the public generally that should they get involved in any dispute with the executive or with each other, they can be sure of a fair and patient hearing and that their disputes will be determined impartially and honestly in accordance with law and justice...